A classic Christmas : a collection of timeless stories and poems.: a collection of timeless stories and poems. (2019) - Dickens, Charles, 1812-1870; Alcott, Louisa May, 1832-1888; Montgomery, L. M (Lucy Maud), 1874-1942; Andersen, H. C (Hans Christian), 1805-1875; Stowe, Harriet Beecher, 1811-1896; Moore, Clement Clarke, 1779-1863; Browning, Elizabeth Barrett, 1806-1861; Longfellow, Henry Wadsworth, 1807-1882; Dunbar, Paul Laurence, 1872-1906; Rossetti, Christina Georgina, 1830-1894; Deland, Margaret, 1857-1945; Baer, Libbie C, 1848-1929; et al.
No abstract available